2007
DOI: 10.1128/jb.00457-07
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic AMP Directly Activates NasP, an N -Acyl Amino Acid Antibiotic Biosynthetic Enzyme Cloned from an Uncultured β-Proteobacterium

Abstract: The cyclic AMP (cAMP)-dependent biosynthesis of N-acylphenylalanine antibiotics by NasP, an environmental DNA-derived N-acyl amino acid synthase, is controlled by an NasP-associated cyclic nucleotide-binding domain and is independent of the global cAMP signal transducer, cAMP receptor protein. A 16S rRNA gene sequence found on the same environmental DNA cosmid as NasP is most closely related to 16S sequences from ␤-proteobacteria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 27 publications
0
21
0
Order By: Relevance
“…Two NasYs (NasY6 and NasY10, both from group 2) show low-level similarity (ϳ15% identity) to individual N-acylhomoserine lactone synthases (4); however, the majority of NAS enzymes do not show similarity to known enzymes, and none is predicted to contain the Pfam "autoinducer synthetase" domain PF00765 that is commonly found in N-acylhomoserine lactone synthases. There are two known N-acylphenylalanine-producing NASs, NasP1 and NasP2 (NasA), that are nonhomologous to one another and lack similarity to the NasYs (12,13). There are also singular examples of N-acyltryptophanproducing (NasW) and N-acylarginine-producing (NasR) NASs, neither of which resembles other previously described NAS enzymes (7).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two NasYs (NasY6 and NasY10, both from group 2) show low-level similarity (ϳ15% identity) to individual N-acylhomoserine lactone synthases (4); however, the majority of NAS enzymes do not show similarity to known enzymes, and none is predicted to contain the Pfam "autoinducer synthetase" domain PF00765 that is commonly found in N-acylhomoserine lactone synthases. There are two known N-acylphenylalanine-producing NASs, NasP1 and NasP2 (NasA), that are nonhomologous to one another and lack similarity to the NasYs (12,13). There are also singular examples of N-acyltryptophanproducing (NasW) and N-acylarginine-producing (NasR) NASs, neither of which resembles other previously described NAS enzymes (7).…”
Section: Resultsmentioning
confidence: 99%
“…Extracts of antibacterially active eDNA clones have yielded several distinct varieties of N-acyl amino acids, including N-acyl derivatives of tyrosine, phenylalanine, tryptophan, and arginine ( Fig. 1, compounds 1 to 4, respectively) (6,7,12). eDNA clones that produce N-acyl amino acids have been identified in metagenomic studies spanning geographically and compositionally distinct soils, suggesting that N-acyl amino acid-producing bacteria may be common to the majority of soil ecosystems.…”
mentioning
confidence: 99%
“…Binding of c-di-GMP to a PilZ domain usually affects the cellular physiology through modulation of protein-protein or protein-DNA interactions, but a direct effect on the catalytic activity of enzymes involved in alginate and cellulose biosynthesis was also shown 56 57 . NasP, a metagenome-derived NAS, was shown to be activated by c-AMP, another widespread bacterial secondary messenger 58 . Therefore, we propose a role of the c-di-GMP binding PilZ domains for the regulation of Nas354 and Nas343 activity; the detailed mechanism needs to be further explored.…”
Section: Discussionmentioning
confidence: 99%
“…HPLC-MS analysis coupled with 1 H NMR studies of the two most abundant chemical species isolated from these ethyl acetate extracts indicated that the major clone-specific compounds produced by EC5 are spectroscopically and chromatographically identical to the 12-carbon N-acyl derivative of phenylalanine (observed m/z ϭ 348.2) and to the 14-carbon N-acyl derivative of tryptophan (observed m/z ϭ 415.3) (see Fig. S1 in the supplemental material) (7,9).…”
Section: Resultsmentioning
confidence: 99%